IMPORTANCE AND SIGNIFICANCE OF PUBLIC RELATIONS IN EDUCATION - Narančić Joveljić, Branislava (ACADEMIC REVIEW, 2023)
All institutions today are under the watchful eye of the public. Educational institutions are not exempt from this either. They must apply different strategies of public relations in order to communicate with the public at a high level. This work explains in a reviewed manner the importance and importance of relations with the public in educational institutions. The contribution of this paper is in the clarification of the way in which communication is applied in educational institutions with an emphasis on improving the reputation of that educational institution. This is done for the reason that there are fewer and fewer students and educational institutions must present themselves in the best possible light in order to attract students and students. In this way, relations with the public help the educational institution achieve its primary goal, which is education.